Market Orientation and Innovativeness in Supply Chains: Supplier's Impact on Customer Satisfaction. Issue 3 (2nd April 2013) - Kibbeling, Mirjam; van, Hans; van, Arjan
<x xml:space="preserve">Abstract</x> As today's firms increasingly outsource their noncore activities, they not only have to manage their own resources and capabilities, but they are ever more dependent on the resources and capabilities of supplying firms to respond to customer needs. This paper explicitly examines whether and how firms and suppliers, who are both oriented to the same customer market, enable innovativeness in their supply chains and deliver value to their joint customer. We will call this customer of the focal firm the "end user." The authors take a resource‐dependence perspective to hypothesize how suppliers' end‐user orientation and innovativeness influence downstream activities at the focal firm and end‐user satisfaction. The resource dependence theory looks typically beyond the boundaries of an individual firm for explaining firm success: firms need to satisfy customer demands to survive and depend on other parties such as their suppliers to achieve customer satisfaction. Accordingly, the research design focuses on three parties along a supply chain: the focal firm, a supplier, and a customer of the focal firm (end user). The results drawn from a survey of 88 matched chains suggest the following. First, customer satisfaction is driven by focal firms' innovativeness. A focal firm's innovativeness depends, on the one hand, on a focal firm's market orientation and, on the other hand, on its suppliers' innovativeness. Second, no relationship could be established between a focal firm's market orientation and a supplier's end‐user orientation. Market orientation typically has within‐firm effects, while innovativeness has impact beyond the boundaries of the firm. These results suggest that firms create value for their customer through internal market orientation efforts and external suppliers' innovativeness.